Algebraic structure and basics of analysis of n-dimensional quaternionic space - Altun, Deniz; Yuce, Salim (ELSEVIER SCI LTD, 2021)
In this study, we focused on n-dimensional quaternionic space H-n. To create the module structure, first part is devoted to define a metric depending on the product order relation of R-n. The set of H-n has been rewritten with a different representation of n-vectors. Using this notation, formulations corresponding to the basic operations in H-n are obtained. By adhering these representations, module structure of H-n over the set of real ordered n-tuples is given. Afterwards, we gave limit, continuity and the derivative basics of quaternion valued functions of a real variable.
Keywords: Symplectic geometry; n-Dimensional quaternionic space; Componentwise multiplication; Science & Technology - Other Topics